Overview of Motor Vehicle Density in Relation to Noise Levels on Malioboro Street - Prasetyawati, Naris Dyah; Huda, Said Naufan; Sudaryanto, Sigid; Bagyono, Tuntas (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2025)
Population growth can generate various activities that consequently lead to an increase in transportation facilities. This condition is closely associated with the high purchasing power of the community toward motor vehicles as a means of transportation. The increase in the number of motor vehicles has serious environmental impacts, particularly noise pollution. Noise is defined as unwanted sound generated by activities or operations at certain levels and durations that may cause disturbances, thereby interfering with and/or endangering human health. Traffic noise that exceeds permissible standards can result in negative impacts on people conducting activities around the noise source. In general, noise can adversely affect health, causing physiological, psychological, communication, balance disorders, and hearing-related effects. This study aimed to obtain information on noise levels along Malioboro Street in 2021. The research employed a descriptive observational survey design. The study was conducted along Malioboro Street, with samples collected at three observation points: Point I (Malioboro Sign Entrance Gate), Point II (in front of Taman Batik Terang Bulan Store), and Point III (Yogyakarta Zero Kilometer Point). Data collection was carried out for one week. The results showed that traffic density and noise intensity were directly proportional to the noise levels on Malioboro Street, with an average vehicle volume of 1,703.2 units/day and an average noise level of 70 dBA. The study concludes that most of the measurements exceeded the permissible noise standard for commercial and service areas, which is 70 dBA, across the three observation points per day.